ANALISIS PENGARUH UKURAN KAP, TENURE KAP TERHADAP AUDIT REPORT LAG (ARL) DENGAN KAP SPESIALISASI INDUSTRI SEBAGAI VARIABEL MODERASI - Cahyaningrum Giyanto, Sinta; Rohman, Abdul (Diponegoro Journal of Accounting, 2018)
This research aims to examine the factors that affect audit report lag (ARL) of financial reports  of the manufacturing companies listed on Indonesia Stock Exchange. The dependent variable in this research is audit report lag (ARL). The examined factors of this research are audit firm size and audit firm tenure as independent variables, auditor industry specialization as moderating variable, profitability, leverage, and company size as control variables.            This sample consists 56 manufacturing companies listed on Indonesia Stock Exchange which submitted annual reports and financial reports to bapepam during 2014-2016. The data used in this research was secondary data. This research used purposive sampling method to select the data. This research hypotesis were tested using multiple regression analysis.Based on the analytical results shows that audit firm size has no significant influence to audit report lag (ARL), audit firm tenure was negatively significant to audit report lag (ARL), auditor industry specialization as moderating variabel has no significant influence to audit report lag (ARL).